The Effect of Knowledge and Ease of Use of Quick Response Code Indonesia Standard (QRIS) on the Decision to Use E-Wallet as a Payment Means in UMKM in Yogyakarta City - Gunawan Gunawan; Rudianto Rudianto; Sediatmoko Sediatmoko; Marisi Pakpahan (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
The use of QRIS in MSMEs in Yogyakarta has increased and spread to small MSMEs. This makes the development of payment services more advanced and easier. However, there are also quite a few small MSMEs or consumers who still have minimal knowledge about QRIS and how to use it. For this reason, it is necessary to know the extent of knowledge about QRIS and what benefits can be obtained from QRIS. Socialization of QRIS is very helpful in the development of QRIS in the community, especially among MSMEs in Yogyakarta. The purpose of this study is to determine the knowledge and responses of culinary MSME consumers in Yogyakarta about the Quick Response Code Indonesia Standard (QRIS) and its ease of use. In this study, the author used a descriptive quantitative research method with a data collection method using a questionnaire based on the Likert Scale. While the data research process uses descriptive analysis, associative analysis which includes multiple linear regression analysis, correlation coefficient analysis and determination coefficient analysis, and hypothesis testing in the form of simultaneous tests (F Test). Furthermore, describing the results of the analysis using descriptive sentences.